Book Review: Being Mortal: Illness, Medicine and What Matters in the End - Sue Sutton (The Beryl Institute, 2015)
In her review of Being Mortal: Illness, Medicine and What Matters in the End written by Atul Gawande, MD, Sue Sutton shares both the insights of Dr. Gawande and their important perspectives for person-centered experience. She reinforces that in this day of increased focus on understanding patient's expectations and patient-focused care, Dr. Gawande compels us to learn how to have the difficult conversations about what really matters. She closes the review with a compelling quote from the author, "I never expected that among the most meaningful experiences I'd have as a doctor- and, really, as a human being- would come from helping others deal with what medicine cannot do as well as what it can."